The problem of Gush Emunim - Ahlberg, Sture (Nordisk judaistik, 1979)
A movement that has made big headlines lately is the Gush Emunim, a term which means "bloc of believers". The enormous publicity about this phenomenon in the mass media has made necessary a close study to the issues connected with the Gush Enunim movement. In this paper I intend to give a more detailed account of the background of this movement, and above all, deal with some terminological questions connected with it. The earliest roots of Gush Emunim may be traced to the period after the Israeli victory in the Six-Day War 1967. The formal founding of the movement, however, goes back to February 1974, when several hundred yeshivah-students and young members of the National Religious Party attended a convention at Kfar Ezion. The ideology originated, to no small degree, from that of Rabbi Kook. In Rabbi Kook’s mind the idea of the Jews’ affinity with the Holy Land played a tremendous role. Only in Palestine could the Jewish people fulfill the divine mission to become a "light for the nations". In spite of the abundant use of religious symbols and conceptions, mainly derived from Jewish eschatology, it must be regarded as quite misleading to designate this movement as a Messianic one. Gush Emunim, then, is basically a political, nationalistic movement, devoted to the aim of refusing territorial compromises with the Arabs concerning the Land of Israel.